Efeito do solvente extrator sobre a atividade antioxidante do resíduo da produção comercial de polpa de maracujá (Passiflora edulis) e aplicação do extrato otimizado ao óleo de soja - Hauagge, Márcia Aurora Bulgarelli (2023)
The recycling of residues is an environmental and economic need for the juice industry, one alternative to solve this problem would be the antioxidants extraction. Antioxidants are substances that can decrease or prevent the oxidation of molecules, biological systems, and foods. In this study it was evaluated the effect of different solvents extractors under activity of antioxidants discards of the juice pulp industry. The extracts were prepared using the solvents ethanol, isopropanol, ethyl acetate and their binary and ternary mixtures, according to the methodology of experimental planning for mixtures. Analyses were made using the DPPH, FRAP methods to determinate the antioxidant activity and evaluated the percentage of phenolic and flavonoid compounds. With the obtained results from the analysis, it was concluded that the most antioxidant amount was on the extract with the mixture of ethyl acetate + ethanol, whereas in the ethyl acetate + ethanol + isopropanol mixture had the higher result in the FRAP analysis. Afterwards, it was determinate the composition of extractor solvent that showed the best antioxidant activity (desirable function), and the assay were repeated). It was observed that with the optimized extract the DPPH result was higher than expected, for FRAP and total phenolics the result was extremely close to the foretold value; The obtained result from the flavonoids was higher than expected. The optimized extract was also tested in soy oil, through oxidative induction time (OIT), aiming to determinate the level of thermal stability of the mixture so that it was possible to evaluate its preservation period. In this analysis the passionfruit optimized extract showed to be competitive with the BHT solution, which is an artificial antioxidant. In the FTIR analysis, the resulting data for the identified functional groups demonstrate good similarity between the oil with BHT and the oil with passion fruit extracts. In high performance liquid chromatography, the concentration of p-cumaric acid was higher when compared with others compounds present in the extract.